The Effect of Hydrogen on the Parameters of Plastic Deformation Localization in Low Carbon Steel; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Lunev A. G. Alexey Gennadievich; Nadezhkin M. V. Mikhail Vladimirovich; Shlyakhova G. V.; Barannikova S. A.; Zuev L. B. (2014, 2014)
Title screen